LAYANAN BIMBINGAN KLASIKAL BERBASIS ONLINE MELALUI TEKNIK MODELING UNTUK KEMATANGAN KARIER SISWA SMP - Tira Tartila; Ecep Supriatna; Rima Irmayanti (IKIP Siliwangi, 2023)
Classical guidance is a guidance and counseling service that has the aim of launching service activities that develop students' potential to achieve educational goals. One of the techniques that can be used in the implementation of classical guidance services is the symbolic modeling technique. The symbolic modeling technique is a technique that is carried out by showing a video or film in which a character who has behavior or activity can be imitated by an individual who sees it. The purpose of this study is to find out how the implementation, the responses of BK students and teachers, as well as the obstacles experienced by BK students and teachers in the implementation of online-based classical guidance services through modeling techniques for career maturity of class IX students. The approach taken is a qualitative approach with a descriptive method. The data collection technique used is the method of observation, interviews, and documentation. The results of this study indicate that the modeling technique used in this classical guidance service can assist students in planning their further education after graduating from junior high school.Keywords: Career maturity, Junior high school students